Le paysage comme outil de gouvernance pour un territoire métropolitain - Laurent Lelli; Charlotte Rozier; Pierre Enjelvin; Christine Descœur; Christel Griffoul; Gwenaëlle Dubois (Développement Durable et Territoires)
The Clermont Vichy Auvergne metropolitan area initiated a process of consultation and cooperation with the actors of this territory under construction. Place of discussion and cooperation between inter-municipal territories, supported by local stakeholders keen to maintain a balanced development of the territory, the project approach remains to be invented. To consider its future, the Urban Planning and Development Agency of Clermont Metropole decided to contribute to this reflection by implementing an original initiative of local animation entitled : “workshop landscapes in situ”. Using various experts, these workshops helped to characterize the metropolitan area’s landscapes, to share their views and to reproduce the visions produced. With the help of various experts, these workshops helped to characterize the landscapes of the metropolitan area, to share their views and to define guidelines for the territorial project.